Modulation of the amyloidogenic pathway by a novel β-secretase inhibitor (F70hab16) from Malaysian Endophyte Cytospora Rhizophorae, in murine models for alzheimer’s disease / Richard Muhammad Johari James - James, Richard Muhammad Johari (Institute of Graduate Studies, UiTM, 2014)
Alzheimer’s disease (AD) is the most common form of dementia. Until recently, AD is managed by relieving the cognitive symptoms without addressing one of the purportedly fundamental causes of the disease which is the formation of the amyloid plaques. The deposition and aggregation of β-amyloid are key events in the onset, progression and pathogenesis of AD. Thus one of the emerging strategies in treating AD is to inhibit the enzyme responsible for the formation of amyloid plaques, which is β-site amyloid cleaving enzyme (BACE-1). Endophytes are currently viewed as an outstanding source of bioactive natural products and may provide BACE-1 inhibitors as potential drug candidates for the treatment of AD. A novel bioactive compound, F70HAB16 was successfully isolated from a local endophytic strain and was found to inhibit the BACE-1 enzyme in vitro (IC50=13 μM). Oral treatment with 5 mg/kg of F70HAB16 for 14 days in scopolamine-induced memory deficit mice model was found to restore memory impairment caused by scopolamine in the radial arm maze and Morris water maze (MWM) tasks.